2009
DOI: 10.1007/s10151-009-0550-y
|View full text |Cite
|
Sign up to set email alerts
|

Stapled ileostomy closure results in reduction of postoperative morbidity

Abstract: Functional end-to-end anastomosis reduces operating time and morbidity compared to conventional ileostomy takedown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 10 publications
4
65
0
3
Order By: Relevance
“…The characteristics of the included trials are summarised in Table 1. Two randomised clinical trials (RCTs) [14,15] described their randomisation technique. The former study also described its blinding technique, but Löffler et al [15] had not blinded the patients or surgeons.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of the included trials are summarised in Table 1. Two randomised clinical trials (RCTs) [14,15] described their randomisation technique. The former study also described its blinding technique, but Löffler et al [15] had not blinded the patients or surgeons.…”
Section: Resultsmentioning
confidence: 99%
“…To exclude selection bias, we aimed to analyse the data of randomised control trials only. However, one RCT had no leak in their cohort of patients (Hull et al [18]) and a second RCT (Shelygin et al [14])…”
Section: Complications Datamentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies have recently shown that the difference in equipment cost is offset by the operative time saved when constructing a stapled anastomosis [22,23,24]. Furthermore, the larger luminal diameter achieved following a stapled ileal anastomosis results in significantly decreased rates of postoperative small bowel obstruction and ileus (and their associated costs) when compared to sutured anastomoses [24,25,26]. Therefore, standardizing patients undergoing EC to all receive stapled anastomoses may lead to further cost reductions.…”
Section: Discussionmentioning
confidence: 99%
“…Routine closure of the stoma can be performed using either a hand-sewn end-to-end anastomosis or various techniques using staples [3][4][5]. The theoretical advance of stapled anastomosis over the other techniques is the potentially shorter operative time and the larger luminal diameter, thereby being less associated with postoperative small bowel obstruction [3].…”
Section: Introductionmentioning
confidence: 99%